Macro- Language Policy and Planning and Lack of Proficiency in Language Learning and Use by Nigerian Students - Adegbite, Wale (2014)
In this study, the problem of' non-proficiency in language learning and use among Nigerian students is investigated. Using empirical data and information from available literature on the subject as evidence, it was observed that the language deficiencies of the students could be attributed to the lack of fit between the formulation of the national (macro-) language policy and planning and implementation procedures, in view of the complexity of the socio-cultural, multilingual and multi-ethnic context of the nation. The perceptions of students' language deficiencies at different levels of education were described and the attendant effects on national development stated. A "bottom-top" proposal was then made for initial prioritization of micro-language policies and planning procedures that would later provide bases for viable macro-policy and planning projects.